Quality of Life of Patients with Head and Neck Cancer Receiving Cetuximab, Fluorouracil, Cisplatin Comparing to Cetuximab, Fluorouracil, Cisplatin, and Docetaxel within the CEFCID Trial - Goerling, Ute; Gauler, Thomas; Dietz, Andreas; Grünwald, Viktor; Knipping, Stephan; Guntinas-Lichius, Orlando; Frickhofen, Norbert; Lindeman, Hans Walter; Fietkau, Rainer; Haxel, Boris; Große-Thie, Christina; Maschmeyer, Georg; et al. (Oncology Research and Treatment, 2022)
Introduction: CeFCiD was a multicenter phase II study comparing the efficacy of cetuximab (C), 5-flourouracil, and cisplatin with the same regimen adding docetaxel (D) in recurrent/metastatic head and neck cancer. The primary analysis trial did not demonstrate survival benefit from therapy intensification in first-line recurrent and/or metastatic squamous cell carcinoma of the head and neck (SCCHN). The current analysis of the trial assessed the impact of treatment on quality of life (QoL). Methods: The European Organization for Research and Treatment of Cancer Quality of life Questionnaire QLQ-C30 and the tumor-specific module for head and neck cancer (QLQ-H&N35) were used to assess QoL at baseline (visit 1), after 2 (visit 3), 4 (visit 5), and 6 (visit 7) cycles of chemotherapy. Results: Of 180 patients included in this study, 86 patients (47.8%) completed the questionnaires at baseline. Considering selected scores over treatment time, there was no difference in global QoL, dyspnea, swallowing, and speech between the treatment arms in the course. For fatigue, a significant increase from baseline to visit 3 (p = 0.02), visit 5 (p = 0.002), and to visit 7 (p = 0.003) was observed for patients receiving D, cisplatin or carboplatin (P), 5-fluorouracil (F), and C. At the end of chemotherapy, the manifestation of fatigue was similar compared in the 2 treatment arms. Discussion/Conclusion: Therapy intensification not adversely affects selected scores of QoL of patients with recurrent and/or metastatic SCCHN. Nevertheless, fatigue seems to be pronounced in patients treated with D.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Docetaxel; Head and neck cancer; Quality of life; Recurrent and metastatic; Therapy intensification